2023
DOI: 10.1002/mus.27783
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic peripheral nerve cross‐sectional area in adults, excluding median and ulnar nerves: A systematic review and meta‐analysis

Abstract: Introduction/Aims Although electromyography remains the “gold standard” for assessing and diagnosing peripheral nerve disorders, ultrasound has emerged as a useful adjunct, providing valuable anatomic information. The objective of this study was to conduct a systematic review and meta‐analysis evaluating the normative sonographic values for adult peripheral nerve cross‐sectional area (CSA). Methods Medline and Cochrane Library databases were systematically searched for healthy adult peripheral nerve CSA, exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…In this issue of the journal, Eby and colleagues present a metaanalysis that collates 67 studies with published reference values of sonographic nerve sizes of various upper and lower extremity nerves. 17 The median and ulnar nerves were excluded from their study, as the authors indicate "the body of literature in this area is extensive and has been reported previously," including results of imaging in the longitudinal plane and data from pediatric populations. 18,19 The overview they provide shows a wide range of reported normal nerve sizes for the different nerves.…”
Section: Various Sets Of Reference Values Have Been Published For Manymentioning
confidence: 99%
“…In this issue of the journal, Eby and colleagues present a metaanalysis that collates 67 studies with published reference values of sonographic nerve sizes of various upper and lower extremity nerves. 17 The median and ulnar nerves were excluded from their study, as the authors indicate "the body of literature in this area is extensive and has been reported previously," including results of imaging in the longitudinal plane and data from pediatric populations. 18,19 The overview they provide shows a wide range of reported normal nerve sizes for the different nerves.…”
Section: Various Sets Of Reference Values Have Been Published For Manymentioning
confidence: 99%